Reviewing the current practice of professional fees for civil and structural engineering consultancy services [electronic resource] - 439506 Salehin Salleh (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2007